Interferencias morfosintácticas del finés en las producciones en español de escolares bilingües - Ansó Ros Judith (Septentrio Academic Publishing, 2022)
ABSTRACT. The article analyses the main morphosyntactic interference of Finnish in the productions in Spanish of students of two types of bilingual education: bilingual school and mother tongue maintenance courses. The data collection took place in two different periods, separated by a period of two years. Bilingual students present a strong influence of the dominant language, Finnish, which is reflected in their linguistic productions, both oral and written. The analysis shows that the major morphosyntactic interferences are centred in four different types: gender errors, wrong use of prepositions, wrong use of some verbs and verbal time and omission of articles. The results show how the number of interferences carried out by bilingual schoolchildren decreases over time, revealing the inversely proportional relation between the number of interferences and competency, evidencing an incomplete acquisition of their minority language. Keywords. Interferences; language acquisition; bilingualism; Finnish-Spanish; morphosyntax; incomplete acquisition